Addressing COVID-19 Vaccine Hesitancy in Patients with IBD. Issue 3 (24th September 2021) - Hudhud, Dania; Caldera, Freddy; Cross, Raymond K
Lay Summary: It is recommended that all patients with IBD undergo vaccination against COVID-19. In this commentary, we encourage IBD providers to serve as vaccine advocates and suggest implementing different methods for battling misinformation, paying careful attention to minority population.